Global prevalence of antibiotic resistance in blood-isolated Enterococcus faecalis and Enterococcus faecium: a systematic review and meta-analysis - Jabbari Shiadeh SM; Pormohammad A; Hashemi A; Lak P (Infection and Drug Resistance, 2019)
Seyedeh Marzieh Jabbari Shiadeh,1 Ali Pormohammad,2 Ali Hashemi,1 Parnian Lak31Department of Microbiology, School of Medicine, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 2Student Research Committee, Department of Microbiology, School of Medicine, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 3Department of Cell and Tissue Biology, University of California San Francisco, San Francisco, CA, USACorrespondence: Ali PormohammadClinical Microbiology, Shahid Beheshti University of Medical Sciences, Koodakyar Street, Tabnak Blv, Yaman Avenue, Chamran Highway, Tehran, IranTel +98 212 387 2556Fax +98 212 243 9964Email pormohammadali@yahoo.comIntroduction: One of the global concerns is the increasing trend toward antimicrobial resistance and the consequent lack of efficient antimicrobials. Nosocomial infections present a big threat for patients all over the world and treatment with broad-spectrum antibiotics leads to outgrowth of hospital-associated resistant Enterococci clones that are very important in bloodstream infections. We surveyed the frequency and time trend of antibiotic resistance in Enterococci blood isolates from hospitalized patients in different regions of the world.Methods: Literature from January 1, 2000 to May 20, 2018 was searched systematically using Medline (via PubMed), Embase, and Cochrane Library and all original publications on the antibiotic resistance prevalence in blood-isolated Enterococci strains with standard laboratory tests were included. Quality of the included studies was assessed with the modified Critical Appraisal Checklist recommended by the Joanna Briggs Institute. Depending on the heterogeneity test, we used either random or fixed effect models to assess the appropriateness of the pooled prevalence of drug resistance.Results: A total of 291 studies were enrolled in the meta-analysis. Between all antibiotics, based on the WHO original offices, American countries showed the lowest prevalence of resistance for linezolid in Enterococcus faecalis. Regarding the prevalence of vancomycin resistance, Western Pacific, European, and American countries had the lowest level of resistance and South-East Asia and Eastern Mediterranean countries showed the highest level of resistance. Moreover, our findings for Enterococcus faecium indicated that America and South-East Asia had the lowest and the highest levels of resistance for linezolid, respectively.Conclusion: Based on our findings, the prevalence of vancomycin-resistant E. faecium in bloodstream infections is significantly high, especially in Eastern Mediterranean countries, which is a massive warning signal for resistance to this broad-spectrum antibiotic. Therefore, the establishment of appropriate antibiotic usage guidelines should be essential in these countries.Keywords: drug resistance, Enterococcus faecalis, Enterococcus faecium, prevalence, meta-analysis